Investigation of internal nozzle flow, spray and combustion characteristics fueled with diesel, gasoline and wide distillation fuel (WDF) based on a piezoelectric injector and a direct injection compression ignition engine. (5th March 2017) - Yu, Wenbin; Yang, Wenming; Zhao, Feiyang
Highlights: The behaviours of piezoelectric and solenoid injectors were compared. The macroscopic characteristics of test fuels including spray penetration, spray velocity and spray angle were investigated. The internal flow turbulence and cavitation were taken into account for spray simulation. KIVA4 and CHEMKIN codes were coupled to solve the chemical reaction for engine combustion simulation. Abstract: In this work, the internal nozzle flow, spray, combustion and emission characteristics of traditional diesel, gasoline and two kinds of WDF (gasoline/diesel blend fuel and kerosene) were comprehensively and systematically investigated based on a piezoelectric injector and a direct injection compression ignition engine. In fuel spray study, the behaviours of piezoelectric and solenoid injectors were compared. The macroscopic characteristics of test fuels including spray penetration, spray velocity and spray angle were investigated. A so-called "full cavitation model" was used for internal nozzle flow and cavitation simulation, wherein the characteristics such as turbulent kinetic energy and injection velocity are investigated. The simulation results of fuel internal nozzle flow are convincing to explain the experimental results of spray. In the combustion and emissions study, the KH-RT model which takes into account the cavitation and turbulence was used for spray prediction. KIVA4 and CHEMKIN codes are coupled to solve the chemical reaction. Two chemical reaction models, which have been developed by authors' group in previous study, were used for investigating two combustion strategies, i.e., partially premixed combustion (PPC) and highly premixed combustion (HPC) fueled with traditional diesel, gasoline and two kinds of WDF. From the results, it can be inferred that, compared with diesel and gasoline, WDF is more suitable for utilization in compression ignition engines at present stage.